Analisis Pertumbuhan Dan Persebaran Penduduk Provinsi Sumatera Utara Berdasarkan Hasil Sensus Penduduk Tahun 2010 - Pinem, Mbina (Universitas Negeri Medan, 2014)
This research porposes to understand growth and spread of population in Province of North Sumatra. The method used here is decriptive analysis of secondary data with the spatial approach. Whereas the object of research are the number of population, the population growth, and spread of population of North Sumatra Province based on 2010 census of Indonesian pupulation. The outcome of research represents that the population growth of Province of North Sumatra from 2000 to 2010 average of 1,22 percent per year. Then, the highest population growth found in Regency of Middle Tapanuli (2,46 percent), followed by Regency of Karo (2,17 percent), and South Tapanuli Regency (2,12 percent). Meanwhile the lowest population growth found in Siantar Town (-029 percent) and followed by Toba Samosir Regency (0,38 percent) and Simalungun Regency (-0,46 percent). As the spread of pupulation in the North Sumatra Province is not prevalent, as the settlements spreads nearly 62,87 percent on the east coast region, whereas only 3,05 percent on the west coast, and the rest 4,85 percent on the Nias Islands.